Disentangling the complex relation of disability and depressive symptoms in old age – findings of a multicenter prospective cohort study in Germany. (30th January 2017) - Hajek, André; Brettschneider, Christian; Eisele, Marion; Lühmann, Dagmar; Mamone, Silke; Wiese, Birgitt; Weyerer, Siegfried; Werle, Jochen; Fuchs, Angela; Pentzek, Michael; Stein, Janine; Luck, Tobias; et al.
ABSTRACT: Background: Most of the previous studies attempted to disentangle the relationship between disability and depressive symptoms were limited to observation periods of only few years. Moreover, evidence is missing regarding the complex co-occurrence of disability and depressive symptoms in old age in Germany. In order to close the research gap, we aimed at disentangling the complex co-occurrence of disability and depressive symptoms in old age in Germany over a longer time frame. Methods: Based on data from a representative survey of the German general population aged 75 years and older, the course of disability as well as depressive symptoms was observed every 1.5 years over six waves. While disability was quantified by the Lawton and Brody Instrumental Activities of Daily Living scale, the Geriatric Depression Scale was used to measure depressive symptoms. Taking into account the complex co-occurrence of depressive symptoms and disability, a panel vector autoregressive model was used. By taking the first differences, unobserved heterogeneity was taken into account. Results: In the total sample and in both sexes, we revealed a robust positive association between an initial change in depressive symptoms and subsequent changes in disability. No robust association between an initial change in disability and a subsequent change in depressive symptoms was detected. Conclusion: Our findings highlight the importance of changes in depressive symptoms for future changes in disability in old age.